Fermentation of Dairy-Relevant Sugars by Saccharomyces, Kluyveromyces, and Brettanomyces: An Exploratory Study with Implications for the Utilization of Acid Whey, Part II - Viviana K. Rivera Flores; Timothy A. DeMarsh; Patrick A. Gibney; Samuel D. Alcaine (Fermentation, 2022)
In Greek-style yogurt production, every kilogram of product yields 2 to 3 kg of acid whey (YAW); this coproduct’s composition and low pH pose challenges for its proper valorization and reinsertion into the food supply chain. However, 240 mL of YAW contains over 9 g of lactose and represents a good source of minerals; these traits can be leveraged to develop nutritious fermented beverages. The purpose of this study is to investigate the aerobic fermentation of dairy sugars by different yeasts by characterizing these processes and their products. This will determine whether such methods provide viable options for the production of acetic-acid-containing beverages from YAW. To achieve this, yeast nitrogen base was used to prepare four growth media formulations, each supplemented with lactose, glucose, galactose, or a 1:1 mix of glucose and galactose (GLU:GAL), and each adjusted to a pH of 4.20. Fermentations were performed by pure cultures of S. cerevisiae, K. marxianus, B. claussenii, or B. bruxellensis, and were held at 25 °C with agitation at 185 rpm. For each treatment, density, pH, and microbial enumeration were measured over time to obtain process profiles, while ethanol, organic acids, and sugars were analyzed at the beginning and the end of each fermentation via HPLC, to determine resulting products. ANOVA and Tukey’s honest significant difference test at a significance level of 0.05 were used to compare residual sugars and fermentation products. Variable rates of sugar consumption were observed for each species. In GLU:GAL, B. claussenii consumed all of the glucose, left behind most of the galactose, and produced a high concentration of acetic acid. These results suggest the potential to develop versatile processes that target glucose for acetic acid production, while leaving available galactose to confer products with prebiotic properties. The development of processes for the conversion of YAW into beverages with organic acids and other healthful components not only aligns with consumers’ demands for better-for-you products, but also promotes the valorization of this otherwise underutilized dairy coproduct.